2013
DOI: 10.5812/ijem.8088
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Improves the Survival of INS-1 Cells by Promoting Macroautophagy

Abstract: BackgroundType 2 diabetes mellitus (T2D) is a metabolic disease characterized by dysfunction of pancreatic beta cell and insulin resistance. Liraglutide, which has many special anti-diabetes biological effects, is found to inhibit beta cell death and ameliorate endoplasmic reticulum stress (ERs) induced by free fatty acid (FFA). Macroautophagy (hereafter referred to as autophagy) altered by FFA is also associated with the dysfunction or death of pancreatic beta cells.ObjectivesWe aim at proving that Liraglutid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Moreover, Sharma et al demonstrated that GLP-1 reduced the fat load in hepatocytes by increasing the rate of autophagosome and autophagolysosome formation, i.e., autophagic flux [ 37 ]. Consistent with a previous study, autophagy has been reported to play a protective role in PA-induced cell death and alleviate the lipid burden in INS-1 cells [ 38 ]. Thus, we confirmed that palmitate induced autophagy in rat insulin-secreting cells, which is related to the pathogenesis of T2D.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, Sharma et al demonstrated that GLP-1 reduced the fat load in hepatocytes by increasing the rate of autophagosome and autophagolysosome formation, i.e., autophagic flux [ 37 ]. Consistent with a previous study, autophagy has been reported to play a protective role in PA-induced cell death and alleviate the lipid burden in INS-1 cells [ 38 ]. Thus, we confirmed that palmitate induced autophagy in rat insulin-secreting cells, which is related to the pathogenesis of T2D.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, liraglutide has been shown to protect against NAFLD in both human trials and cellular models . Throughout these investigations, liraglutide has been demonstrated to have lots of effects, including enhancing cell survival through promoting autophagy, inhibition of inflammation, attenuation of endoplasmic reticulum stress and so on; however, the precise molecular mechanisms are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Third, activation of the glucagon-like peptide-1 (GLP-1) receptor or treatment with a DDP-4 inhibitor triggers AMP-activated protein kinase (AMPK) signaling [ 22 , 23 , 24 ], which facilitates autophagy [ 5 , 9 , 15 , 18 , 25 ]. In fact, a GLP-1 analog, liraglutide, has been shown to promote autophagy in non-cardiac cells [ 26 ]. Fourth, it has been reported that the activity of circulating DPP-4 is associated with left ventricular dysfunction in patients [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%